Qur’anic intertextuality as discursive strategy in Bayt Baws by Ibrahim Muhammad Talha: A critical discourse analysis - Salma Ali Salem Mansoor; Nur Hasaniyah; Zeid bin Smeer; Muhammad Yusril Firdausi Nuzula; Wala bin Subait (Diwan: Jurnal Bahasa dan Sastra Arab, 2026)
Although Qur’anic intertextuality in contemporary Arabic literature has attracted increasing scholarly attention, studies examining its role in contemporary Yemeni fiction remain limited, particularly those employing critical discourse analysis as their primary analytical framework. To address this gap, this study aims to identify the forms of Qur’anic intertextuality in Bayt Baws and analyze their functions in constructing narrative meaning and articulating socio-political critique. Employing a qualitative research design grounded in Fairclough's three-dimensional critical discourse analysis, this study systematically analyses seven representative excerpts from the novel. It classifies them according to Miftāḥ's typology of Qur’anic intertextuality. The findings reveal that Qur’anic intertextuality in Bayt Baws operates through external intertextuality, in which direct Qur’anic quotations provide symbolic authority and ethical weight to the narrative, and internal intertextuality, in which indirect Qur’anic resonances engage the reader's moral consciousness through implicit thematic engagement. These mechanisms function as deliberate discursive strategies to expose political corruption, critique social hypocrisy, and foreground moral contradictions between Qur’anic ideals and contemporary Yemeni realities. This study contributes to Arabic literary studies by demonstrating how Qur’anic intertextuality serves as a tool for reshaping narrative discourse and enhancing critical awareness, while extending the scope of Qur’anic intertextuality research into the largely underexplored domain of contemporary Yemeni literature.